Youth victim perspective: optimizing presentation of patient-reported outcomes in a violence intervention program - Ashley Hollo; Mark Nimmer; Brooke Cheaton; Marlene Melzer-Lange; Michael Levas (BMC, 2023)
Abstract Introduction The health, well-being and psychological development of children in urban areas is threatened by exposure to interpersonal violence. Violence intervention programs, such as Project Ujima, provide children with comprehensive treatment following exposure to violence. Services focus on the interruption of the violence cycle, mental health, and developing resiliency. The collection of patient-reported outcomes (PROs) from youth victims of violence informs community-based, programmatic, and individual participant interventions. Although the collection of PROs throughout treatment has been demonstrated to be feasible, youth and crime victim specialist preferences for data presentation is unknown. We sought to determine patient and crime victim specialist preferences regarding which PROs are of interest and how best to visually display them for optimal engagement. Results Fifteen youth and nine crime victim specialists consented to participate. Both preferred visuals with the highest level of color-shading and descriptions. The domains with the highest level of interest among both youth and case workers were social, anger, emotional, school, physical, peer relations, and psychosocial well-being. Youth and crime victim specialists expressed low interest in positive affect, meaning/purpose, physical stress experience, and depression domains. Youth wanted to see their scores compared to others in the program, while crime victim specialists did not think such comparisons would be beneficial. In contrast to youth, crime victim specialists believed youth should see their physical functioning and PTSD scores. Conclusion Youth participants and their crime victim specialists in a violence intervention program desired to see their PROs in a graphical form and agreed on their preference for many of the domains except for PTSD and physical functioning. Both groups preferred visuals with the highest level of shading and descriptions. Further investigation is needed to determine how to implement PRO visuals with the desired domains into regular violence intervention programming. Methods Participants in Project Ujima's 8-week summer camp, ages 7-18 years, who were either a victim of violent injury, a direct relative of a violent injury victim, or a homicide survivor were recruited for this qualitative study. Crime victim specialists, who work directly with these youth throughout the year, were also recruited to participate. We conducted structured interviews to determine which parameters and visual formats were of highest interest and best understood by youth participants and crime victim specialists.